2020
DOI: 10.3390/antiox9121300
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Glutathione Peroxidase-1 Knockout on Anticancer Drug Sensitivities and Reactive Oxygen Species in Haploid HAP-1 Cells

Abstract: The role of glutathione peroxidases (GPx) in cancer and their influence on tumor prognosis and the development of anticancer drug resistance has been extensively and controversially discussed. The aim of this study was to evaluate the influence of GPx1 expression on anticancer drug cytotoxicity. For this purpose, a GPx1 knockout of the near-haploid human cancer cell line HAP-1 was generated and compared to the native cell line with regards to morphology, growth and metabolic rates, and oxidative stress defense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
(44 reference statements)
1
7
0
Order By: Relevance
“…A previous study reported a hyperploidy‐selective efficacy of paclitaxel in the haploid‐diploid HAP1 mixed culture at a drug concentration (15 n m ) similar to that observed in this study [ 11 ] (Fig. 2 ), and another study reported an IC 50 value of paclitaxel in HAP1 cells (~ 3 n m ) close to the value obtained in this study [ 44 ] (Fig. 1 ).…”
Section: Discussionsupporting
confidence: 89%
“…A previous study reported a hyperploidy‐selective efficacy of paclitaxel in the haploid‐diploid HAP1 mixed culture at a drug concentration (15 n m ) similar to that observed in this study [ 11 ] (Fig. 2 ), and another study reported an IC 50 value of paclitaxel in HAP1 cells (~ 3 n m ) close to the value obtained in this study [ 44 ] (Fig. 1 ).…”
Section: Discussionsupporting
confidence: 89%
“…In particular, the fact that both HAP-1 and the GPx1-negative knockout variant responded similarly throughout the biological assays indicated a negligible impact of GPx1 expression on the cytotoxic mechanism of pentathiepins. Previous studies already compared these two cell lines with regards to their metabolism and antioxidant capacity, including several enzymes and intracellular GSH levels [ 22 ]. Additionally, we detected that catalase was most abundant in HAP-1, HAP-1.KO.GPx1, and the pancreatic cancer cell line DanG.…”
Section: Resultsmentioning
confidence: 99%
“…However, chemotherapeutic resistance mechanisms have been linked to increased expression of GPx1 [ 21 ]. Moreover, in a recent publication, GPx1 knockout cells proved to be significantly more sensitive to treatment with the chemotherapeutics cisplatin, lomustine, and temozolomide compared with the parental cell line [ 22 ]. Hence, therapeutic inhibition of the GPx1 may be a promising approach for potentiating cancer chemotherapy in drug-resistant cells, one which could be pursued by using pentathiepins.…”
Section: Introductionmentioning
confidence: 99%
“…Another reported that MDR overexpressing cancer cells were more sensitive to tiopronin than native cells. Thus, tiopronin could find an additional indication in cancer therapy [15] .…”
Section: Discussionmentioning
confidence: 99%